Pendeta Za'ba : education for the upliftment of the Malays - Hashim, Rosnani (The Other Press, 2010)
ZA'BA IS A WELL KNOWN MALAYSIAN FIGURE I language and literature. This is evident from the title of Pendeta (learned scholar) bestowed upon him in 1956 and the honorary degrees conferred to him by universities for his work in NIalay language and literature. In fact, he began writing in 1916 to improve the Malay Language and he was a member of the committee ·which was set up to work on the Malay language (BM) as the National Language of Malaya and also to standardise Bahasa IvIelayu and Bahasa Indonesia in 1959. However, it is incorrect to see Za'ba's role to be merely just that when in fact he had also given a lot of thoughts and contributions on other matters such as education, economy, religion and politics.